Identification of Freshwater Algae from Kufrah, Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
The Libyan freshwater algae remains partially unexplored in term of their distribution. Many reports done on algae in south of Libya, but recently need more new reports. A survey of farms in kufra was undertaken from October 2010 to May 2011. Out of 16 sites of water bodies surveyed from different farms. Among the sampling sites there were algal blooms comprising 24 species following to 24 genera and 5 divisions were recorded.  Chlorophyta, Cyanophyta, Bacillariophyta, Euglenophyta and Dinophyta.  Chlorophyta was the most dominant, followed by Cyanophyta. They were observed as scums or mat on the surface of water bodies.
Keywords: freshwater algae; Cyanophyta; Chlorophyta; Bacillariophyta; Euglenophyta